Joint Multicast and Unicast Beamforming for Coded Caching - Zhong, Shan; Wang, Xiaodong (IEEE transactions on communications, 2018)
In this paper, we consider a multicell system with cache-equipped base stations (BSs) and users. A coded caching scheme is employed at user ends such that multiple requested file contents can be combined and encoded together at the BS, and decoded successfully at the users. The BSs can then multicast the coded cached content and unicast the uncached content to users. Two different system models are proposed based on different levels of BS cooperation. We formulate the joint multicast and unicast beamformer design problem to maximize the weighted user fairness rate subject to the per BS power constraint. We propose a Riemannian conjugate gradient algorithm to solve the problem, which operates on the multi-sphere manifold of the parameter space and has a low computational complexity but better performance compared with the existing semi-definite relaxation methods. Extensive simulation results are provided to demonstrate the performance of the proposed systems.